Geopolitical and geoeconomic factors in India’s Central Asia policy (International relations and international law Journal, 2019)
The dissolution of the Soviet Union towards the end of 1991 has led to the emergence of five Central Asian Republics (CARs) of the former Soviet Union, namely, Kazakhstan, Kyrgyzstan, Uzbekistan, Tajikistan, and Turkmenistan, as independent countries. The strategic location of this region at the crossroads between Europe and China and also between Russia and Iran coupled with their huge and largely untapped reserves of oil and gas enabled the region to impart immense geo-strategic importance in world affairs. Countries of the region and beyond have tried their best to influence the newly independent countries to actualise their respective interests. The US, Europe, Russia and China as well as Japan and Korea all have formulated their policies with a view to influence the regional geopolitics of the region. But a massive country towards the south of Central Asia was sitting idly having a low profile in the region with the tag of latecomer. Historically, deep rooted civilizational linkages, thorough friendship, cultural affinity and economic bondage largely remained disconnected throughout the years between these two Asian neighbours until recently. Neither the Central Asian countries nor India felt any compelling need to include each other in their geopolitical calculus. Against this background, this research article argues that India has vital economic and security interests in the CARs and needs to develop a comprehensive, long-term strategy to protect and promote its geo-political interest in this region.Key words: Soviet Union, Central Asian Republics, geopolitics, economic and security interests.